An Inventory of Ornamental Plants in The Home Yards of The Community of Ujumbou Village Sirenja Sub-District and Their Utilisation as Learning Media - Annisa Fadillah; Musdalifah Nurdin; Lilies N. Tangge (CV. Dharma Samakta Edukhatulistiwa, 2025)
This research aims to describe the types of ornamental plants in the yard of the Ujumbou Village community and produce learning media that are suitable for use. This type of research is descriptive qualitative using exploration method with free sampling technique. The results of the study obtained 76 types of ornamental plants from 37 families and 56 genus found in Ujumbou Village. Assessment of learning media in the form of pocket books conducted by each expert lecturer obtained a score of 82.85% material experts, 97.5% design experts, 69.23% media experts, and 92.25% student trials. The average percentage obtained was 85.45%. These results indicate that the pocket book that has been made is very feasible to use as learning media.